The Comparison of the Sensation Seeking Level, Coping Strategies and Vulnerability to Stress among MMT Treated Addicts and Normal Group - Nezamaldin Ghasemi; Mahdi Rabiei; S Ali Haqayeq; Hasan Palahang (Drug Control Headquarters, Research and Education Office, 2011)
Introduction: The purpose of this research was to investigate the relationship between the level of sensation seeking and coping strategies as well as vulnerability to stress among addicts who are under MMT treatment and normal group. Method: This research was a causal comparative study. The population of the study was all addicts of Baharestan city of Esfahan province who were referred to addiction treatment clinics. The sample was selected by clustering random sampling. (62 addictes and 52 normal participants) Results: The MANOVA results showed a significant difference among the three variables of sensation seeking, vulnerability to stress and mindful problem solving coping strategy within the two groups. Multiple regression results also showed meaningful differences between level of sensation seeking and the kind of used drug and also between support seeking coping strategy and mindful problem solving. Conclusion: The sensation seeking level and the amount of stress vulnerability may be significant predictors of the kind of coping strategy and kind of substance in substance abusers. It can be used in predictive and therapical interventions to apply them in practical sectors better.